An Analysis ofStudents’ Video Assignments: A Case of EFL Students ata Public University - Cholny, Rath; Sovann, Ly; Yikpoa, Hang; Sreynich, Rath; Rynna, Vann (English Education Postgraduate Program, Universitas Negeri Manado, 2024)
Video assignments become an increasingly popular tool in education nowadays. It offers students a dynamic and engaging way to demonstrate their understanding and performance. This research focuses on the students' analysis of EFL students' video assignments. The aims of this research are to find out how much the students understand assignment and how well they manage the contents of their videos. Qualitative research and video analysis framework were used in this study to collect and analyse the data of the EFL students who study in their third year at the research site. The eight videos were adopted from the EFL students to analyse and collect the data. The study found three elements of videos structure such as introduction, body, and conclusion of the videos.Ã‚Â EFL students greeted audiences, introduced topic, structure, expectation and engaged interests in the introduction part of the video. During the videos, students mostly used body languages, facial expression, voice of tone, pronunciation and topic comprehension. However, students missed using some contents in the conclusion of the videos comprising quotation, recommendation, and asking for giving comments from audiences for the improvement of their videos. Additionally, this study may serve as a reference or motivation for further research in the same area. This research suggests future researchers to focus on vid1eo analysis in different context, participants, and analytical framework to minimize the research gaps. Classroom teachers should use these results to improve the quality of video assignments in their class.